2024
DOI: 10.3390/ma17102301
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties and Water Permeability of Pervious Planting Concrete: A Study on Additives and Plant Growth

Juan He,
Shanhansu Xu,
Guochen Sang
et al.

Abstract: Pervious planting concrete (PPC) is in line with the concept of ecological environmental protection. However, due to its own porous structure, it is difficult to obtain excellent mechanical properties and water permeability at the same time, which hinders its promotion and application. In this paper, natural gravel (NG), ordinary Portland cement (OPC), polyvinyl alcohol latex powder (PVAP) and polycarboxylate superplasticizer (PS) were used to prepare the PPC, and its mechanical properties and water permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Haji et al [34] indicated that pervious concrete exhibits better permeability when the fly ash content is 0%-5%; when the fly ash content is 5%-25%, the permeability of pervious concrete shows a declining trend. Considering that the permeability of pervious concrete can well characterize the continuous porosity [35], this experiment obtained the same trend with fly ash content ranging from 10% to 30%. The order of influence of three response factors on the pH value o logical concrete is fly ash content > design porosity > water-binder ratio stood from the previous variance analysis that the interaction between W/B, F, and P is not statistically significant.…”
Section: Analysis Of Continuous Porositysupporting
confidence: 60%
“…Haji et al [34] indicated that pervious concrete exhibits better permeability when the fly ash content is 0%-5%; when the fly ash content is 5%-25%, the permeability of pervious concrete shows a declining trend. Considering that the permeability of pervious concrete can well characterize the continuous porosity [35], this experiment obtained the same trend with fly ash content ranging from 10% to 30%. The order of influence of three response factors on the pH value o logical concrete is fly ash content > design porosity > water-binder ratio stood from the previous variance analysis that the interaction between W/B, F, and P is not statistically significant.…”
Section: Analysis Of Continuous Porositysupporting
confidence: 60%